Learning together: the effects of inclusion of students with disabilities in mainstream schools - Aline Krüger Dalcin (EconomiA, 2023)
Purpose: This article aims to analyze the impact that the inclusion of students with disabilities has on the achievement of their schoolmates and to analyze the impact that this inclusion has on the achievement of the students with disabilities themselves. Design/methodology/approach: The author begins investigating how the inclusion of students with disabilities in regular schools affects achievement of schoolmates. To answer this research question, the author explores the natural variation in time in the number of students with disabilities and use data from National Exam of Upper Secondary Education (Enem). Then, the author investigates how the inclusion affects achievement of the students with disabilities themselves and uses propensity score matching methodologies and, again, data from Enem. Findings: The results show that an additional percentage point in the proportion of students with disabilities would reduce schoolmates' writing scores by a 0.0031 standard deviation. In other subjects, the author finds weak or none evidence of a significant peer effect. In addition, using Propensity Score Matching methodologies, the results show that the mean scores are up to 44% of a standard deviation, which is higher among students with disabilities enrolled in regular schools compared to those who are enrolled in special schools. In summary, the evaluation is that inclusion policies achieve the goal of improving the performance of students with disabilities but such policies have a small and adverse side effect. Originality/value: For this reason, the present study proposes to fill this gap in the literature by analyzing the impact of the inclusion of students with disabilities on both groups. In addition, this paper contributes to the empirical literature of peer effect with an analysis of the peer effect of students with disabilities per competency. Finally, the article is important given the existence of few articles in Brazil on the topic of education and people with disabilities.
Keywords: 330; Education; Disabilities; Inclusion